Kata Kunci “Asbabun Nuzul” dalam Database Dimensions dengan Menggunakan Teknik Bibliometrik - Iqrimatunnaya Iqrimatunnaya (Gunung Djati Conference Series, 2023)
There is no research that comprehensively examines the mapping of the development of asbabun nuzul, which is the background of this research. This study aims to discuss the asbabun nuzul keyword in database dimensions. This research uses quantitative methods with bibliometric techniques. The asbabun nuzul study is still developing, existing, and being studied by many experts so that it continues to produce various kinds of discussion and research results. In the research category, the keyword asbabun nuzul is the most researched by the field of Philosophy and Religious Studies by publishing 152 articles. The existence of the development of publications regarding nuzul asbabun tends to increase every year with the highest number of studies occurring in 2020 by publishing 129 articles. The researcher who plays the most active role in conducting research on asbabun nuzul himself is Wely Dozan, he has published 6 articles. The At-Tibyan Journal of Al-Qur'an Science and Tafsir is the most existing place of publication by publishing 19 articles. This study concludes that dimensions are able to examine the asbabun nuzul keyword comprehensively.